Evaluation of CBD and THC content in indoor-grown Cannabis sativa cv. MK 2021 flowers for medical use - Gargaglione, Veronica Beatriz; Birgi, Jorge Alberto; Arregui, María Emilia (Ediciones INTA, 2024)
Cannabis sativa L. has been widely used for medicinal purposes due to the content of specific molecules called cannabinoids. CBD (cannabidiol) is one of the most known cannabinoids for medicinal ends, showing a great potential in therapeutics for childhood epilepsy. In Argentina, cannabis cultivation was prohibited until 2017, when Law No. 27350 was enacted, allowing research using cannabis plants for medicinal use. This gave rise to the need of studying cannabis production and management conditions. To obtain high-quality commercial pharmaceutical products indoor technology is recommended since it allows the control of environmental variables. The aim of this study was to evaluate the CBD and THC content in indoor-grown Cannabis sativa cv. MK 2021 flowers, and their changes according to main and lateral branches. Seeds were sown in phenolic foam cubes and, after 28 days, 46 plants were transplanted to a hydroponic system, composed of 20-liter buckets containing nutrient solution. The crop cycle lasted 105 days. On February 14, the plants were harvested and a total of 10 plants were randomly selected for morphologic measurements and determination of cannabinoids content (%). Plants reached a final height of 119.9 (±10.1) cm. The mean biomass of the flower produced was 52 g/plant, while that of the leaves and roots was 13.3 and 41.6 g/plant respectively. Significant differences were found in the percentage of CBD in the flowers according to the position of the branches: the main branches had higher concentrations than the lateral branches. CBD values varied from 9.5% to 13.65%. In contrast, no differences were found in the percentage of THC according to the position of the branches, with values around 0.7 and 1.6%. This study presents the first results on indoor Cannabis production for medical purposes in south Argentina. This information is very relevant considering that the medicinal cannabis industry may show potential as a new commercial product.